Metformin and other glucose-lowering drug initiation and rates of community-based antibiotic use and hospital-treated infections in patients with type 2 diabetes: a Danish nationwide population-based cohort study. Issue 8 (19th August 2016) - Mor, Anil; Petersen, Irene; Sørensen, Henrik T; Thomsen, Reimar W
Abstract : Objective: Data on early risk of infection in patients receiving their first treatment for type 2 diabetes are limited. We examined rates of community-based antibiotic use and hospital-treated infection in initiators of metformin and other glucose-lowering drugs (GLDs). Design: Population-based cohort study using medical databases. Setting: General practice and hospitals in Denmark. Participants: 131 949 patients with type 2 diabetes who initiated pharmacotherapy with a GLD between 2005 and 2012. Exposure: Initial GLD used for pharmacotherapy. Main outcome measures: We computed rates and adjusted HRs of community-based antibiotic use and hospital-treated infection associated with choice of initial GLD with reference to metformin initiation, using an intention-to-treat approach. Results: The rate of community-based antibiotic use was 362 per 1000 patient-years at risk (PYAR) and that for hospital-treated infection was 51 per 1000 PYAR. Compared with metformin, the risk of hospital-treated infection was slightly higher in sulfonylurea initiators (HR 1.12, 95% CI 1.08 to 1.16) and substantially higher in insulin initiators (HR 1.63, 95% CI 1.54 to 1.72) initiators after adjustment for comorbid conditions, comedications and other confounding factors. In contrast, virtually no difference was observed for overall community-based antibiotic use (HR 1.02, 95% CI 1.01 to 1.04, for sulfonylurea initiators; and 1.04, 95% CI 1.01 to 1.07, for insulin initiators). Conclusions: Rates of community-based antibiotic treatment and hospitalisation for infection were high in patients receiving their first treatment for type 2 diabetes and differed with the choice of initial GLD used for pharmacotherapy.